2022
DOI: 10.1111/cdoe.12741
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the enablers and barriers of career satisfaction among Australian oral health therapists

Abstract: Objectives This qualitative study explored the enablers and barriers of career satisfaction among Australian oral health therapists (OHTs) and the reasons behind career changes. Methods Participants were recruited in 2 ways: 1) recruitment posts were made on the Facebook pages of two professional groups; and 2) an email was sent to the Doctor of Dental Medicine students of the University of Sydney School of Dentistry, inviting those with OHT qualifications to participate. Each participant completed a semi‐stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Poor remuneration was the leading factor influencing the participants’ decision to leave the dental therapy profession. These results are similar to those reported in a study conducted among Australian oral health therapists, which mentioned low remuneration as a barrier to recruitment and retention [ 28 ]. In contrast, another study conducted among non-working dental therapists in Australia reported family commitments and career change as the leading reasons for attrition, while only 14% of participants cited poor pay [ 15 ].…”
Section: Discussionsupporting
confidence: 90%
“…Poor remuneration was the leading factor influencing the participants’ decision to leave the dental therapy profession. These results are similar to those reported in a study conducted among Australian oral health therapists, which mentioned low remuneration as a barrier to recruitment and retention [ 28 ]. In contrast, another study conducted among non-working dental therapists in Australia reported family commitments and career change as the leading reasons for attrition, while only 14% of participants cited poor pay [ 15 ].…”
Section: Discussionsupporting
confidence: 90%
“…Finally, another series of articles focused on various enablers or components of dental hygienist job/career satisfaction. This included two from Korea [ 76 , 77 ], and one each from Australia [ 78 ], Japan [ 79 ] and the USA [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with similar studies conducted in South Africa, the UK and New Zealand. 32,33,34 However, these sources of dissatisfaction are not universal among dental therapists. For instance, Australian dental therapists reported satisfaction with the work itself, supportive environment, career development, autonomy and professional recognition.…”
Section: Discussionmentioning
confidence: 99%
“…The state as the employer sees dental therapists as instruments of cheap labour just as apartheid aimed it to be. (Male,34).…”
Section: Leadership Viewed Us As Second-class Dentists Who Are Also I...mentioning
confidence: 99%